Ten major issues in American politics - Hofstatter, Richard (Oxford, 1968)
In the main, the Introduction to the original edition of this work will serve to introduce the reader to its possible uses. But it may help in understanding its purposes to say a bit more about its inception. In 1956, representatives of the Fund for Adult Education approached me with the proposal that author prepare a brief documentary collection, suitable for the use of adult discussion groups, on a limited number of fundamental issues of the American past and present. In some respects the format was suggested to me, though the choice of selections was entirely my own and author was entirely free to make whatever introductory comments author chose. It was considered desirable to discuss certain issues in their broad est aspects, cutting across the historical conditions under which they arose. For example, the question concerning the extension of the right of suffrage-who shall vote?-was treated as it affected not only the achieve ment of universal male suffrage in the early nineteenth century but also the newly liberated slaves during and after Reconstruction, and as it affected women later on. No historian would pretend that these three situations are alike or in every respect comparable, but the purpose of treating them together was to focus discussion upon the idea of suffrage and citizenship in its broadest aspect. It was the hope of the Fund for Adult Education that the documents would cause readers to look at the issues involved in their general philosophical implications as well as in their particular settings.
Keywords: Political Science